Mononuclear cells and vascular repair in HHT - Dingenouts, Calinda K. E.; Goumans, Marie-José; Bakker, Wineke (Frontiers in Genetics, 2015)
Hereditary hemorrhagic telangiectasia (HHT) or Rendu–Osler–Weber disease is a rare genetic vascular disorder known for its endothelial dysplasia causing arteriovenous malformations and severe bleedings. HHT-1 and HHT-2 are the most prevalent variants and are caused by heterozygous mutations in endoglin and activin receptor-like kinase 1, respectively. An undervalued aspect of the disease is that HHT patients experience persistent inflammation. Although endothelial and mural cells have been the main research focus trying to unravel the mechanism behind the disease, wound healing is a process with a delicate balance between inflammatory and vascular cells. Inflammatory cells are part of the mononuclear cells (MNCs) fraction, and can, next to eliciting an immune response, also have angiogenic potential. This biphasic effect of MNC can hold a promising mechanism to further elucidate treatment strategies for HHT patients. Before MNC are able to contribute to repair, they need to home to and retain in ischemic and damaged tissue. Directed migration (homing) of MNCs following tissue damage is regulated by the stromal cell derived factor 1 (SDF1). MNCs that express the C-X-C chemokine receptor 4 (CXCR4) migrate toward the tightly regulated gradient of SDF1. This directed migration of monocytes and lymphocytes can be inhibited by dipeptidyl peptidase 4 (DPP4). Interestingly, MNC of HHT patients express elevated levels of DPP4 and show impaired homing toward damaged tissue. Impaired homing capacity of the MNCs might therefore contribute to the impaired angiogenesis and tissue repair observed in HHT patients. This review summarizes recent studies regarding the role of MNCs in the etiology of HHT and vascular repair, and evaluates the efficacy of DPP4 inhibition in tissue integrity and repair.